2016
DOI: 10.21927/ijnd.2016.4(1).29-40
|View full text |Cite
|
Sign up to set email alerts
|

Riwayat KEK dan anemia pada ibu hamil tidak berhubungan dengan kejadian stunting pada anak usia 6-23 bulan di Kecamatan Sedayu, Bantul, Yogyakarta

Abstract: cant (p=0.13, OR:1.5,. The CED history during pregnancy was not the risk factor of the stunting incident (p=0.23, OR:0.7,. Other factors related to the stunting incidence were mother 's height (p=0.01, OR:2.04,, the history of low birth weight (p=0.03, OR:3.03, and food insecurity (p=0.04, OR:2.7,. The multivariate analysis showed that mother's height was correlated with the stunting incidence in Sedayu subdistrict. Conclusion: Factors that infl uence the incidence of stunting in children aged 6-23 month were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
2
8
0
6
Order By: Relevance
“…However, there was no significant relationship between upper arm conference and stunting incidence (p= 0.986). The same result occurred in Warsini et al (2016) which showed that there was no significant relationship between upper arm conference and stunting incidence (p = 0.23). The study showed that the research subjects had a high awareness of routine antenatal care so that chronic energy deficiency could be immediately intervened with supplementary feeding (PMT).…”
Section: Discussionsupporting
confidence: 54%
“…However, there was no significant relationship between upper arm conference and stunting incidence (p= 0.986). The same result occurred in Warsini et al (2016) which showed that there was no significant relationship between upper arm conference and stunting incidence (p = 0.23). The study showed that the research subjects had a high awareness of routine antenatal care so that chronic energy deficiency could be immediately intervened with supplementary feeding (PMT).…”
Section: Discussionsupporting
confidence: 54%
“…Analisis Warsini et al (2016) terhadap 126 kasus dan 126 kontrol di Kecamatan Sedayu, Kabupaten Bantul dilakukan hingga tahap multivariat (19).…”
Section: Hubungan Imd Dengan Stuntingunclassified
“…Studi ini memperhitungkan banyak variabel penting dalam analisis bivariatnya yang meliputi kelompok variabel riwayat kesehatan ibu hamil (5 variabel), riwayat kesehatan anak (6 variabel), karakteristik responden (8 variabel). 2016), tidak menemukan adanya hubungan yang signifikan antara waktu pertama pemberian MP-ASI dengan stunting (18,19).…”
Section: Hubungan Imd Dengan Stuntingunclassified
“…The high rates of stunting, wasting and undernourished in West Papua, East Nusa Tenggara and Papua are influenced by the low quality and less variety of food consumed by the community and the lack of socialization about the importance of health in the community (BKP 2009). In addition, the level of hunger or chronic lack of energy in pregnant women can cause nutrition problems e.g infants with low birth weight (Warsini et al 2016). This then leads to stunting during future growth (Supriyanto et al 2018).…”
Section: Evaluation Of Food and Nutrition Security Level Based On Thementioning
confidence: 99%